2001
DOI: 10.7748/ns2001.04.15.29.33.c3006
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the myth of the 12-hour shift: a pilot evaluation

Abstract: This study illustrated the potential a new nursing shift pattern involving 12-hour shifts has for patient care, as well as for staff job satisfaction and efficient management of the ward. Twelve-hour shifts are infamous in nursing and many studies cite exhausted and dissatisfied staff as a reason for the negative press (Fitzpatrick et al 1999, Todd et al 1993). In particular, Todd et al (1989) claimed that the quality of patient care was negatively affected on wards that used a 12-hour shift pattern. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 7 publications
4
41
1
2
Order By: Relevance
“…This result was consistent with previous studies (BloodWorth et al, 2001;Gillespie & Curzio, 1996). Twelve-hour shift pattern has been found to be benefi cial and popular, primarily because it can have social benefi ts (McVicar, 2003).…”
Section: Relevance To Clinical Practicesupporting
confidence: 93%
“…This result was consistent with previous studies (BloodWorth et al, 2001;Gillespie & Curzio, 1996). Twelve-hour shift pattern has been found to be benefi cial and popular, primarily because it can have social benefi ts (McVicar, 2003).…”
Section: Relevance To Clinical Practicesupporting
confidence: 93%
“…A literature review found some studies that concluded that 12-hour shifts can potentially improve nurses` satisfaction , patient care quality and efficient management of the nursing unit (27)(28)(29) . At the same time, it reported potentially serious error-related consequences to patient care (6)(7) .…”
Section: Discussionmentioning
confidence: 99%
“…Although levels of hydration were not assessed, we found evidence of the importance of liquid intake during the shift. Further investigation is necessary.Approximately 25% of the nurses declared to have chosen to work in 12-h shifts in order to have more time, contributing to a more flexible working life (27)(28) . A literature review found some studies that concluded that 12-hour shifts can potentially improve nurses` satisfaction , patient care quality and efficient management of the nursing unit (27)(28)(29) .…”
mentioning
confidence: 99%
“…The majority of health outcomes, and all WLB ones, were self-reported. In a sizeable number of the CWW studies, the intervention was either at the behest of the work force,3436 41 47 49 60 69 70 83 or from the management (with a stated desire to improve health or WLB) 37 50 6264 66 71 74 79 80 82. However, in other studies, the motivation was more obviously efficiency or productivity 46 48 51 53 54 59 61 67 77 78 81.…”
Section: Resultsmentioning
confidence: 99%